(untitled) (The Journal of Psychology and Sociology, 2021)
The article describes the results of a study of the burnout syndrome on the example of Al-Hilal Bank employees and their emotional intelligence for the relationship. Nowadays, employers, like employees, are paying more and more attention to the emotional well-being of employees. Thanks to constant and careful work with personnel and organizational psychology, implemented in Kazakhstani organizations, diagnostics and training work with employees are regularly carried out, which allows identifying cor- rectional targets. One of the most relevant topics for today is the burnout syndrome. To identify the relationship between burnout syndrome and the emotional competence of middle managers, the follow- ing methods were used: “Professional (Emotional) burnout” K. Maslach and S. Jackson in the adaptation of N. Vodopyanova and E. Starchenkova, “EmIn” by D. V. Lyusin. To establish the relationship, the calculation of the Pearson correlation coefficient was used. The study sample included 20 middle-level managers of Al-Hilal Bank aged from 27 to 42 years. The conducted research allows us to draw a general conclusion about the indicators of the respondents’ emotional intelligence, the and their exposure to burnout (emotional and professional), as well as the relationship between these variables. Key words: burnout syndrome, emotional competence, emotional intelligence, middle managers.